2019
DOI: 10.1002/adfm.201907344
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Membrane Production through Polyelectrolyte Complexation Induced Aqueous Phase Separation

Abstract: Nonsolvent induced phase separation (NIPS) is the most common approach to produce polymeric membranes. Unfortunately, NIPS relies heavily on aprotic organic solvents like N-methyl-pyrrolidone. These solvents are unsustainable, repro-toxic for humans and are therefore becoming increasingly restricted within the European Union. A new and sustainable method, aqueous phase separation (APS), is reported that eliminates the use of organic solvents. A homogeneous solution of two polyelectrolytes, the strong polyanion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 33 publications
3
76
0
Order By: Relevance
“…Our research group recently demonstrated that it is also possible to prepare membranes by casting homogeneous PE mixtures instead of coacervates. 47 A switch between two extreme pH regimes was used to control the complexation of a strong polyanion and a weak polycation. Polymer molecular weight, polymer concentration, and coagulation bath salinity were the factors that gave a great control over the membrane structure and resulted in membranes ranging from microfiltration (MF) type to nanofiltration (NF) type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group recently demonstrated that it is also possible to prepare membranes by casting homogeneous PE mixtures instead of coacervates. 47 A switch between two extreme pH regimes was used to control the complexation of a strong polyanion and a weak polycation. Polymer molecular weight, polymer concentration, and coagulation bath salinity were the factors that gave a great control over the membrane structure and resulted in membranes ranging from microfiltration (MF) type to nanofiltration (NF) type.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, a simple change in salt concentration is used to control complexation instead of switching between extreme pH values as was used in our earlier work. 47 Therefore, by use of a salt switch, the membrane formation conditions are milder and the requirement for using a weak and strong PE pair is removed. In this study, a homogeneous mixture of the two strong PEs is prepared at a high salinity where the entropic driving force for complexation is eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cellulose [ 46 ], poly(lactic acid) (PLA) [ 47 ], bamboo fiber, chitosan, and others [ 48 , 49 , 50 , 51 , 52 ]. Green polymers have been investigated to minimize the use of petroleum-derived polymers and meet the performance requirements of membranes [ 53 , 54 , 55 ]. These polymers are derived from natural products, which significantly decrease the carbon footprint of the manufacturing process [ 56 ].…”
Section: Membrane Fabricationmentioning
confidence: 99%
“…One method uses a combination of strong and weak polyelectrolytes. [27,29] In contrast to strong polyelectrolytes, the charge of a weak polyelectrolyte strongly depends on the pH. Therefore, the complexation can be suppressed by adjusting the pH and can be induced by a pH shift.…”
Section: Introductionmentioning
confidence: 99%